Beginning of a Journey of Autologous Stem Cell Transplantation in Combined Military Hospital, Dhaka, Bangladesh (BIRDEM Medical Journal, 2018)
Haematopoietic stem cell transplantation (HSCT) involves the intravenous infusion of autologous or allogenic stem cells collected from bone marrow, peripheral blood or umbilical cord to re-establish haematopoietic function in patients whose bone marrow or immune system is damaged or defective. HSCT are mainly of two types –autologous stem cell transplantation (SCT) and allogenic SCT. Autologous SCT is mainly performed in multiple myeloma, Hodgkin lymphoma, non-Hodgkin lymphoma and less commonly in acute myeloid leukaemia. Haematopoietic stem cells are mobilized from bone marrow to the peripheral blood after the use of mobilizing agents, granulocyte colony stimulating factor (G-CSF) and plerixafor. Then the mobilized stem cells are collected from peripheral blood by apheresis and cryo-preserved. The patient is prepared by giving conditioning regimen (high dose melphelan). Stem cells, which are already collected, are re-infused into patient’s circulation by a blood transfusion set. Engraftment happens 7-14 days after auto SCT. Common side effects of this procedure include nausea, vomiting, diarrhoea, mucositis, infections etc. The first case of SCT performed in Combined Military Hospital, Dhaka, Bangladesh is presented here.Birdem Med J 2018; 8(2): 177-180